Konsep Advokasi Terhadap Anak Korban Perdagangan Anak - Saiful Ansari (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
Child victims of child trafficking in Indonesia need to take action that leads to forms of defense, assistance, protection, and support from various parties. Law number 21 of 2017 concerning the eradication of the criminal act of trafficking in persons in article 35 explains that during the process of investigation, prosecution, and examination at court proceedings, witnesses and/or victims have the right to be accompanied by an advocate and/or other companion needed. The purpose of this paper is to provide an advocacy concept for child victims of child trafficking, for the realization of legal protection. This research is normative legal research using a conceptual approach and a statutory approach. Meanwhile, the results of this study reveal that the concept of advocacy for child victims of child trafficking consists of legal consultation, legal assistance, and legal protection. Meanwhile, the rights of children who are victims of child trafficking that need to be given are reparation rights, compensation rights, restitution rights, and rehabilitation rights.